Efficacy Of The Rotary Instruments In The Removal Of Calcium Hydroxide Intracanal Medicament: An In Vitro CBCT Volumetric Analysis (Journal of Pharmaceutical Negative Results, 2022)
BACKGROUND: The purpose of this study is to evaluate the efficacy of XP Endo Finisher & Master apical file X3 (Protaper Next) used to remove Calcium hydroxide paste from endodontically treated teeth by using CBCT volumetric analysis.AIM & OBJECTIVE: The aim of the study is to evaluate the efficacy of two rotary instruments in the removal of Calcium hydroxide placed as an intracanal medicament.MATERIALS AND METHOD: 60 extracted human mandibular single rooted premolar teeth was selected. All the teeth samples were measured 14 mm from apex &sectioned using diamond disc. Root Canals was prepared using crown-down technique with Protaper Next Rotary NiTi system. The preparation was done upto X3. Calcium hydroxide was inserted into the canals until it extruded through the apex. After storage for 7 days, the specimens were allocated into four groups. Group A: Positive control- In this group Calcium hydroxide was applied but not removed. Group B: Negative control-In this group Calcium hydroxide was not be applied. Group C: Master apical file X3was inserted in rotary motion up to the working length then root canals. Group D: XP Endo finisher was used in continuous motion with 800 rpm & 1 N/cm torque for 1 min with slow 7-8 mm up & down movement to entire length of canal. The CBCT imaging was done for the volumetric analysis of remaining Calcium hydroxide in the canal.RESULT& STATISTICAL ANALYSIS: The efficacy of Calcium hydroxide removal from whole root canals after using Master apical file (Protaper next X3) &XP Endo Finisher showed significant difference. The statistical analysis showed that the mean percentage of oil-based Calcium hydroxide volume removed by XP Endo Finisher was more than Master apical file.CONCLUSION: The XP Endo Finisher removed significantly more root filling material than Master apical file X3 (Protaper Next).